Development of a resilience focused psychoeducation program for families in a disaster prone community - Botor, Nephtaly Joel B.; Cauyan,Jaclyn Marie L.; Gomez, Marie Grace Avelino; Dy, Marison Felicidad R. (Quezon City College of Education, University of the Philippines Diliman, 2019)
This study aimed to develop a manualized eight-week Family Psychoeducation Program (FPP) for families (represented by mother and an adolescent child) in a disaster-prone community.
Thesis
Includes bibliographical references (pages 263-285).
Keywords: Disaster victims -- Counseling of -- Philippines; Disasters -- Philippines